2008
DOI: 10.1002/14651858.cd006564.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine agonist therapy in early Parkinson's disease

Abstract: This meta-analysis confirms that motor complications are reduced with dopamine agonists compared to levodopa, but also establishes that other important side-effects are increased and symptom control is poorer with agonists. Larger, long-term comparative trials assessing patient-rated quality of life are needed to assess more reliably the balance of benefits and risks of dopamine agonists compared to levodopa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 44 publications
2
108
0
2
Order By: Relevance
“…Sedation, nausea, and vomiting can occur but are rarely dose limiting 14 Dyskinesias and motor fluctuations (including the wearing off phenomenon and unpredictable on/off fluctuations) 6 occur in about 40% of patients after five years of treatment. 15 Risk is higher for young onset Parkinson's disease (90% within five years), longer disease duration, and higher levodopa doses.…”
Section: Levodopamentioning
confidence: 99%
See 1 more Smart Citation
“…Sedation, nausea, and vomiting can occur but are rarely dose limiting 14 Dyskinesias and motor fluctuations (including the wearing off phenomenon and unpredictable on/off fluctuations) 6 occur in about 40% of patients after five years of treatment. 15 Risk is higher for young onset Parkinson's disease (90% within five years), longer disease duration, and higher levodopa doses.…”
Section: Levodopamentioning
confidence: 99%
“…Dopamine agonists compared with placebo or levodopa: nausea (NNH=9), somnolence (NNH=8), oedema, (NNH=9), dizziness (NNH=15), vomiting (NNH=34), hallucinations (NNH=22), and hypotension (NNH=48) 6 Impulse control disorders: NNH 10 for patients taking dopamine agonists compared with those not taking dopamine agonists over six months 17…”
Section: Dopamine Agonistsmentioning
confidence: 99%
“…P=0.01), dizziness (1.45, 1.09 to 1.92; P=0.01), hallucinations (1.69, 1.13 to 2.52; P=0.01), and nausea (1.32, 1.05 to 1.66; P=0.02) 98. …”
mentioning
confidence: 94%
“…A different study found a prevalence of hallucinations on antiparkinsonian medication in patients with PD of 46.3% and illusions of 16% 1. Two recent meta-analyses have demonstrated that hallucinations are more frequent among patients with early PD randomised to dopaminergic treatment compared with placebo 3. The most common delusions in patients with PD are paranoid.…”
Section: Introductionmentioning
confidence: 99%